The Effect of Sublethal Concentration of Phosphamidon on Tissue Damage of Nile Fish (Oreochromis niloticliS Trew.) - T Efrizal; Heru Setijanto; Djamar Tumpal F. Lumbanbatu; Yuhara Sukra (Media Veteriner, 1998)
The effect of sublethal concentrations of phosphamidon on tissue damage of nile fish (Oreochromis niloticus Trew.) were studied at the Laboratory of Aquatic Animal Physiology Faculty of Fisheries and at the Laboratory of Anatomy F aculty of Veterinary Medicine Institut Pertanian Bogor. Renewal test method with 40 % of the media renewed everyday was used for the examination of the sublethal toxicity. Each test consisted of 30 nile fish in 15 1 water. The concentrations of phosphamidon used in this study was 0 mg/l (control group), 3.7 mg/l, 7.4 mg/l, dan 11.0 mg/l, respectively, and all groups were repeated three times. Histopathologically, the gill yielded secondary lamella damages, necrosis, hipertrophy, fusion lamella and degeneration of cartilaginous supportive tissue. The intestine showed necrosis of mucous cells, hipertrophy, bleeding in the lamina propria, and proliferation of connective tissue. In the hepatopancreas organ there were bleeding, infiltration of leucocytes and proliferation of connective tissue.